Counseling for Life Skills Development in the Disadvantaged Adult: A Review - Giroux, Roy F.; Pietrofesa, John J. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article provides an overview of research relevant to the disadvantaged adult. A majority of the disadvantaged are excluded from participation in educational programs because of the nature of current educational programs, e.g., prerequisites to training. Inadequate educational background is highly related to unemployment and low aspirational levels. Conversely, low income and a poverty level of life predisposes one to a negative view of education and self. A vicious cycle develops. The implications for education and counseling are explored in terms of (1) a basic education program and (2) life skills development. The thrust of both educator and counselor must be toward specific skill development rather than abstract learnings.